Public Trust and Compliance with the Precautionary Measures Against COVID-19 Employed by Authorities in Saudi Arabia - Almutairi AF; BaniMustafa A; Alessa YM; Almutairi SB; Almaleh Y (Dove Medical Press, 2020)
Adel F Almutairi,1 Ala’a BaniMustafa,1 Yousef M Alessa,1 Saud B Almutairi,2 Yahya Almaleh3 1King Abdullah International Medical Research Center, King Saud Bin Abdulaziz University for Health Sciences, Ministry of National Guard Health Affairs, Riyadh, Saudi Arabia; 2Academic Affairs and Training, Ministry of Health, Riyadh, Saudi Arabia; 3Private Clinics, Riyadh, Saudi ArabiaCorrespondence: Adel F AlmutairiKing Abdullah International Medical Research Center, King Saud Bin Abdulaziz University of Health Sciences, Ministry of National Guard Health Affairs, Riyadh, Saudi ArabiaEmail almutairiad1@ngha.med.saBackground: The newly emerged and highly infectious coronavirus disease (COVID-19), which first broke out in Wuhan, China, has invaded most countries around the globe. As both the daily positive cases and death toll increase, countries have taken aggressive action to halt its spread. Saudi Arabia recognized the danger early and implemented a series of urgent precautions. Thus, this study aims to evaluate public trust and compliance with the precautionary measures implemented by authorities to combat the COVID-19 outbreak.Methods: A cross-sectional study was conducted on a sample of the Saudi public using an electronic questionnaire during the COVID-19 outbreak. The data, which were collected using a validated public trust and compliance tool, were analyzed using the chi-square test, t test, and binary logistic regression.Findings: Of the 1232 participants, there were 655 (53.2%) males and 577 (46.8%) females with 34 ± 10 years as the mean and standard deviation of their age. Participants demonstrated a high level of trust and agreement (98.2%) with the implemented precautionary measures. A positive association between participants’ age and their level of agreement with the government actions (r=˗.082, P=0.004) was observed, with a significant difference between males (97.1± 6.2) and females (98.0± 4.7) (t=˗2.7, P=0.006). Among the participants, 657 (53.3%) were considered to be practicing poor precautionary measures and 575 (46.7%) good precautionary measures. Males (OR=1.8 times, P< 0.001) and those with a school education level (OR=1.7 times, P=0.002) were more likely to have poor precautionary practices compared to others. Married individuals (369, 49.0%; P=0.04) were more likely to comply with good practices.Conclusion: A high level of trust was exhibited by the Saudi public in relation to the precautionary measures taken by authorities in Saudi Arabia. Gender, age, marital status, and educational level were found to be significant factors with regard to compliance with precautionary practices.Keywords: precautionary measures, infectious disease, compliance, public trust